THE PURSUIT OF NEW CHINESE TIMBER STRUCTURE ARCHITECTURE TECHNOLOGY - Yicun, Pang (MATTER: International Journal of Science and Technology, 2018)
Ancient Chinese timber structure architecture technology in the past thousands of years has reached the pinnacle of the state, which also had a profound impact on that of other countries in the world. Unfortunately, the sophisticated technology has not been inherited and improved in the development of Chinese modern architecture, while the reinforced concrete construction has become the main body of the city. Nowadays, Chinese timber structure architecture has a chance of recovery under the language environment, in which new technology and conception of timber structure architecture are being popularized on the global stage. People come to realize the characteristics of timberwork building, namely, energy conservation, environmental protection and good seismic performance, which has a great significance for the future construction of sustainable urban environment. The study of new timber structure architecture technology is the excavation and reapplication of Chinese timber structure construction, which has great theoretical and practical value to the development of timberwork in China. The author will discuss the development history of timber structure architecture in China and main classification of timber structure system. A detailed analysis technological achievements and classic case (Zhongjia Ecology Model District of Exhibition Center in Tianjin, Changzhi Cultural and Creative Industrial Park in Shanxi, etc.) of Chinese new timber structure in the design field will be held in this paper to sum up advantages, problems and countermeasures. This paper also discuss the past and present of timberwork in order to enlighten future application fields and technical route of new timber structure architecture in China.